The benefit of doubt : how confronting your deepest questions can lead to a richer faith - Groeschel, Craig (Zondervan Books, 2025)
"In 'The Benefit of Doubt,' bestselling author and pastor Craig Groeschel shows us that doubt is not the enemy of faith but often an invitation to deeper faith. With his trademark humor, warmth, and lay-it-all-on-the-table style, Groeschel shows how asking questions, seeking answers, and wrestling with doubt can lead to a deeper relationship with God."--